Arctic Ocean, Ellsworth's flying boat, N24 - Ellsworth, Lincoln, 1880-1951 (1925)
"No. 15 Amundsen-Ellsworth 1925 Exped. Trying to get N24 onto an ice "floe" before closing of the big lead." Caption taken from Ellsworth, L., & National Americana Society. (1929). Air Pioneering in the Arctic: the Two Polar Flights of Roald Amundsen and Lincoln Ellsworth (pp. 57, No.15). New York: National Americana Society. Amundson-Ellsworth 1925 Expedition, N 24.